Liver resection for colorectal cancer metastases - Gallinger, S. (Multimed Inc., 2013)
QUESTIONS: 1. Should surgery be considered for colorectal cancer (crc) patients who have liver metastases plus (a) pulmonary metastases, (b) portal nodal disease, or (c) other extrahepatic metastases (ehms)? 2. What is the role of chemotherapy in the surgical management of crc with liver metastases in (a) patients with resectable disease in the liver, or (b) patients with initially unresectable disease in the liver that is downsized with chemotherapy (“conversion”)? 3. What is the role of liver resection when one or more crc liver metastases have radiographic complete response (rcr) after chemotherapy? PERSPECTIVES: Advances in chemotherapy have improved survival in crc patients with liver metastases. The 5-year survival with chemotherapy alone is typically less than 1%, although two recent studies with folfox or folfoxiri (or both) reported rates of 5%–10%. However, liver resection is the treatment that is most effective in achieving long-term survival and offering the possibility of a cure in stage iv crc patients with liver metastases. This guideline deals with the role of chemotherapy with surgery, and the role of surgery when there are liver metastases plus ehms. Because only a proportion of patients with crc metastatic disease are considered for liver resection, and because management of this patient population is complex, multidisciplinary management is required. METHODOLOGY: Recommendations in the present guideline were formulated based on a prepublication version of a recent systematic review on this topic. The draft methodology experts, and external review by clinical practitioners. Feedback was incorporated into the final version of the guideline. PRACTICE GUIDELINE: These recommendations apply to patients with liver metastases from crc who have had or will have a complete (R0) resection of the primary cancer and who are being considered for resection of the liver, or liver plus specific and limited ehms, with curative intent. 1(a). Patients with liver and lung metastases should be seen in consultation with a thoracic surgeon. Combined or staged metastasectomy is recommended when, taking into account anatomic and physiologic considerations, the assessment is that all pulmonary metastases can also be completely removed. Furthermore, liver resection may be indicated in patients who have had a prior lung resection, and vice versa. 1(b). Routine liver resection is not recommended in patients with portal nodal disease. This group includes patients with radiologically suspicious portal nodes or malignant portal nodes found preoperatively or intraoperatively. Liver plus nodal resection, together with perioperative systemic therapy, may be an option—after a full discussion with the patient—in cases with limited nodal involvement and with metastases that can be completely resected. 1(c). Routine liver resection is not recommended in patients with nonpulmonary ehms. Liver plus extrahepatic resection, together with perioperative systemic therapy, may be an option—after a full discussion with the patient—for metastases that can be completely resected. 2(a). Perioperative chemotherapy, either before and after resection, or after resection, is recommended in patients with resectable liver metastatic disease. This recommendation extends to patients with ehms that can be completely resected (R0). Risks and potential benefits of perioperative chemotherapy should be discussed for patients with resectable liver metastases. The data on whether patients with previous oxaliplatin-based chemotherapy or a short interval from completion of adjuvant therapy for primary crc might benefit from perioperative chemotherapy are limited. 2(b). Liver resection is recommended in patients with initially unresectable metastatic liver disease who have a sufficient downstaging response to conversion chemotherapy. If complete resection has been achieved, postoperative chemotherapy should be considered. 3. Surgical resection of all lesions, including lesions with rcr, is recommended when technically feasible and when adequate functional liver can be left as a remnant. When a lesion with rcr is present in a portion of the liver that cannot be resected, surgery may still be a reasonable therapeutic strategy if all other visible disease can be resected. Postoperative chemotherapy might be considered in those patients. Close follow-up of the lesion with rcr is warranted to allow localized treatment or further resection for an in situ recurrence.